Aplikasi Metoda Reciprocal Teaching untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Mata Pelajaran IPA - Yusneli Yusneli (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
This study aims to improve the activity and student learning outcomes in science subjects in class IX.1 SMP Negeri 1 Nan Sabaris. Several conclusions can be drawn from the results of research that has been conducted on IX.1 grade SMPN 1 Nan Sabaris among others, are as follows: (1). Science learning activities of students using Reciprocal Teaching Method experienced an average increase in student activity summarize the material in the first cycle occurred 40.6%. Average student activity asking the question in the first cycle of 34.3%, in the second cycle on average to 81.3% means an increase of 47%. The average activity of students in determining aspects of advanced materials in the first cycle is equal to 21.9% and the second cycle the average is 73.5%, meaning an increase of 51.6%. (2). The average results of students in science subjects has increased where at the end of the first cycle of 34.3% and at the end of the second cycle becomes 80.8%.